FORMULATION AND EFFECTIVENESS TEST OF THE WOUND HEALING GEL RED PIDADA FRUIT (Sonneratia Caseolaris) SKIN EXTRACT - Rusdeni, Sofia; Rini Dwiastuti; Phebe Hendra; Hasyrul Hamzah (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2025)
Red pidada fruit peel extract gel preparation can increase the efficiency and comfort of topical use because of its activity in the healing of open wounds. The aim of this research was to determine how variations in HPMC levels affect the physical quality and stability of red pidada fruit peel extract gel preparations, using the maceration method to obtain thick extracts and formulations with different HPMC concentrations (1% HPMC, 3% and HPMC 5% formula were tested for physical quality and stability, including the Storage Stability Test for 4 weeks. Effectiveness testing was also carried out in white mice using an incision wound method with a depth of 1.5 mm and macroscopic observation. The effectiveness test concentration was set to 5%. The results of data analysis using the Spss One Way ANOVA test showed that higher HPMC levels resulted in a thicker gel, viscosity, stickiness, spreadability, and higher pH. It can be concluded that the gel formulation that meets the requirements is that formula 2 provides organoleptic test results with a thick green color typical of red pidada, good homogeneity test, spreadability test 5.52 cm, adhesion test 2.61 minutes, viscosity test 2700cCps, pH test 4.92. During storage, the gel exhibited good consistency. The longer the storage time, the closer the pH changes to alkaline values. With the Anova value, there is a significant difference in the three formulas with a value of p=0.005 Keywords: red pidada (Sonneratia caseolaris) fruit peel, wound healing, HPMC, gel